Associations between MHC class II variation and phenotypic traits in a free‐living sheep population. Issue 3 (19th November 2021) - Huang, Wei; Dicks, Kara L.; Ballingall, Keith T.; Johnston, Susan E.; Sparks, Alexandra M.; Watt, Kathryn; Pilkington, Jill G.; Pemberton, Josephine M.
Abstract: Pathogen‐mediated selection (PMS) is thought to maintain the high level of allelic diversity observed in the major histocompatibility complex (MHC) class II genes. A comprehensive way to demonstrate contemporary selection is to examine associations between MHC variation and individual fitness. As individual fitness is hard to measure, many studies examine associations between MHC variation and phenotypic traits, including direct or indirect measures of adaptive immunity thought to contribute to fitness. Here, we tested associations between MHC class II variation and five phenotypic traits measured in free‐living sheep captured in August: weight, strongyle faecal egg count, and plasma IgA, IgE and IgG immunoglobulin titres against the gastrointestinal nematode parasite Teladorsagia circumcincta . We found no association between MHC class II variation and weight or strongyle faecal egg count. We did, however, find associations between MHC class II variation and immunoglobulin levels which varied with isotype, age and sex. Our results suggest associations between MHC and phenotypic traits are more likely to be found for traits more closely associated with pathogen defence than integrative traits such as bodyweight and highlight the association between MHC variation and antibodies in wild populations.